Effect of rinsing and ingestion of a carbohydrate solution on maximal sprint performance in competitive male cyclists - Chong, E.; Guelfi, K.; Fournier, P. (Journal of Science and Medicine in Sport, 2011)
Introduction: There is evidence that mouth rinsing or ingesting carbohydrates (CHO) during exercise can improve 1-h high-intensity exercise performance, thus suggesting that the ergogenic effect of CHO is mediated by the stimulation of the sweet taste receptors in the oral cavity. In contrast, we recently showed that CHO mouth rinsing has no effect on sprint performance. Given the presence of sweet taste receptors in the upper intestine (Dyer et al., 2005), the primary aim of this study was to investigate whether the combined stimulation of the taste receptors in the oral cavity and gut can improve the performance of a maximal sprint. Methods: Twelve competitive male cyclists (VO2peak 57.8 ± 4.7 mL/kg·min; mean ± SD) each ingested and rinsed their mouth with 100 mL of one of the following solutions on separate occasions and following a randomised double blind counterbalanced design; (a) 10% glucose solution [Glu], (b) 0.05% aspartame solution [Asp], (c) 9.1% maltodextrin solution [Mal], or (d) water [Wa] as a control, followed by repeatedly mouth rinsing with 11 boluses of 15 mL of the same solution. Then, each participant performed a 45-s maximal sprint effort on a cycle ergometer and performance was assessed. Results: The Asp and Mal trials were not significantly different from Wa across all indicators of sprint performance (maximal power output and mean power outputs, p > 0.05). In contrast, the Glu trial improved maximal power output during the sprint effort by 14.7% (p < 0.05) compared to WA and by 9 and 16% (p < 0.05) compared to the Asp and Mal trials, respectively. Blood glucose levels increased to a similar extent in response to the Wa and Glu trials. Discussion: Our findings suggest that combining the rinsing and ingestion of a glucose solution improves maximal sprint performance. This ergogenic effect is unlikely to be related to sweetness since the Asp trial had no effect on performance despite sweetness matching that of Glu. The benefit of Glu is also unlikely to result from a rise in blood glucose level as Mal resulted in a similar rise but without affecting performance. Given earlier findings from this laboratory that mouth rinsing alone had no effect on maximal sprint performance, we suggest that the ergogenic effect of glucose ingestion on maximal sprint performance is likely to be mediated via the stimulation of the CHO receptors in the esophageal.